Hippocampal AMPARs involve the central sensitization of rats with irritable bowel syndrome. Issue 3 (22nd February 2017) - Chen, Aiqin; Chen, Yu; Tang, Ying; Bao, Chengjia; Cui, Zizhi; Xiao, Meng; Lin, Chun
Abstract: Objective: The roles of hippocampal AMPARs were investigated in irritable bowel syndrome (IBS)‐like rats to clarify the central sensitization mechanisms. Methods: IBS model was induced by neonatal maternal separation. The effects of AMPARs on visceral hypersensitivity were examined by the responses of abdominal muscle to colorectal distension after the bilateral intrahippocampal injections of CNQX (an AMPAR inhibitor). The expressions of hippocampal AMPARs (GluR1 and GluR2) were determined by Western blot. Results: The IBS‐like rats showed visceral hypersensitivity when compared with controls. Bilateral intrahippocampal injections of CNQX alleviated the visceral pain in IBS‐like rats. The maximal effect appeared at the time point of 30 min, and the duration lasted for 90 min after CNQX application, under 40 and 60 mmHg CRD. The expressions of hippocampal GluR2 significantly increased in IBS‐like rats when compared with controls ( p  <   .05). However, the levels of hippocampal GluR1 had no significant differences in rats. Hippocampal LTP induced by HFS was significantly enhanced when compared with controls ( p  <   .05). The expressions of GluR2 significantly increased in the control and IBS‐like rats after 60 min LTP of recordings ( p  <   .05), but not GluR1. Conclusion: Neonatal maternal separation enhances the expression of GluR2 and facilitates the LTP in the hippocampus, which could lead to the formation of visceral hypersensitivity when grown up. Abstract : Intrahippocampal injection of CNQX (an AMPAR inhibitor) alleviated the visceral pain in irritable bowel syndrome (IBS) model rats. The visceral sensitivity, expressions of hippocampal GluR2 and hippocampal LTP significantly increased in IBS model rats when compared with controls. These results imply a possible target for the treatment of IBS.